Pointed bone tools from Bronze Age Stobreč: analyses of raw material, technology, typologyand function (Archaeologia Adriatica, 2026)
This paper presents the first study of a group of pointed bone tools from a recently discovered and partially investigated prehistoric settlement in the area of present-day Stobreč near Split, corresponding to its Middle and Late Bronze Age horizon. Detailed analyses of raw material, manufacturing technology, typology and function were carried out in order to reconstruct aspects of everyday life within this prehistoric community and to deepen the understanding of its economic activities and resource exploitation strategies. The research revealed a predominant use of bones from domestic animals, with evidence of a hunting component. The morphological characteristics of the bones, as well as the developed methods in which they were worked, were crucial for shaping tools such as borers, awls, needles and projectiles. Functional interpretation based on microscopic use-wear analysis indicates the working of hides and plant fibres, as well as textile production and possible use in hunting or warfare. Enriching the modest corpus of prehistoric bone artefacts from the eastern Adriatic coast, this study simultaneously highlights the importance of an interdisciplinary and holistic approach for the comprehensive reconstruction of prehistoric practices.
Keywords: bone artefacts; raw material; technology; typology; functional analysis; Bronze Age; Stobreč; Dalmatia